REPRESENTASI KRITIK SOSIAL DALAM FILM DUA GARIS BIRU(Analisis Semiotika dalam Film Karya Gina S. Noer) - Putra Apriansyah (2021)
The Dua Garis Biru movie is a movie by Gina S. Noer, a teen drama genre released in 2019, which tells about the story of two teenagers namely Bima and Dara who are lovers that still in high school level. At the age of 17, they were reckless have intercourse outside of the marriage. This movie won 5 nominations in the Bandung Film Festival and 2 nominations for the Indonesian Film Festival. In the Dua Garis Biru movie, of course contains many meanings by the filmmaker to be conveyed through Semiotics which are scattered in scene by scene. This is what researchers will try to explore the Dua Garis Biru movie, trying to express the meanings of social criticism either in implicit or explicit meaning as the movie won the Best Original Screenplay Nomination at the Indonesian Film Festival on 8 December 2019. Researchers will use the Roland Barthes Semiotics study as a reference in conducting this research.